(untitled) (Dissertare, 2023)
The study has the purpose of clarifying the foundations of multimodal learning in university education under an andragogical approach, establishing a link with the formation of skills, learning styles and andragogical principles, to develop multimodal strategies in university learning environments.The applied methodology was framed in the qualitative approach, with a documentary design supported by the systematic review technique of various research works published in journals indexed on platforms such as Scopus, Scielo, Latindex, Redalyc, Dialnet, among others. The analysis of documentary information was based on the hermeneutic-critical method, establishing units of analysis as a starting point to derive emerging categories. In this sense, the research findings highlighted the need to substantiate a flexible scheme in university education, to make possible the combination of various ways of learning in a multimodal learning environment, for the development of cognitive, creative and communicative skills. To conclude, the multimodal perspective under an andragogical approach is linked to various learning approaches based on different disciplinary contributions, oriented towards the development of human competencies, which allows learners to be responsible for their own training process towards the search for knowledge, according to the capabilities and needs of each person.